Equestrian communities: design features and development process - Fackrell, Lara L. (Kansas State University, 2008)
Equestrian Communities are platted housing developments that include amenities suited for horse boarding and riding. Since the mid 1970s, this particular sector of amenity community development has become an increasing trend. This study was designed to take a look at the way these communities are designed; where they are located; how they are managed; and, to whom they are marketed. Designing equestrian communities requires knowledge of how these communities are designed, where the land comes from, why people are buying into them and who those people are. Case study methodology was used to gather data on 22 communities across the US. Data sources included review of the marketing websites belonging to the communities; a literature review; and, interviews conducted with individuals responsible for the design and sales of the communities' lots or the management of the equestrian facilities. Statistics and images of the communities, including plats where available, were compiled into community "cut sheets" which are single-page synopses of each community.
Keywords: Landscape architecture; Equestrian community; Amenity community; Neighborhood design; Subdivision; Development; Landscape Architecture (0390)